THE INFLUENCE OF MACROECONOMIC VARIABLES ON INDONESIAN NATURAL RUBBER EXPORTS TO SOUTH KOREA PEROD 1990-2022 - Diah Manik Leontina; Sudarsana Arka (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Indonesia is a country that has abundant natural resources, especially in the agricultural sector. Natural rubber is one of Indonesia's leading export commodities which certainly has considerable potential for the country's economy. Indonesian natural rubber is exported to various countries in the world, especially to South Korea. However, the situation of Indonesia's export volume to South Korea has fluctuated over the last thirty-two years, and is likely to decline in 2017-2022. The objectives of this research are: 1) Analyze the influence of macroeconomic variables, namely prices, exchange rates, GDP per capita and inflation rates simultaneously on Indonesian exports to South Korea for the period 1990-2022. 2) Partially analyze the influence of price, exchange rate, GDP per capita and inflation rate variables on Indonesian rubber exports to South Korea for the period 1990-2022. The analysis technique used is the Error Correction Model (ECM) for time series data with 32 observations obtained through secondary data. The selected models are stationarity testing, cointegration testing, classical assumption testing consisting of normality tests, multicollinearity tests, and heteroscedasticity tests. The results of this research are: 1) International prices, exchange rates, GDP per capita and inflation simultaneously have a significant influence on Indonesia's natural rubber exports to South Korea for the period 1990-2022. 2) International prices in the long and short term have a negative but not significant effect on Indonesian natural rubber exports to South Korea. 3) In the long term, the exchange rate has a negative but not significant effect on Indonesian natural rubber exports to South Korea. Meanwhile, in the short term, the exchange rate has a positive but not significant effect on Indonesia's natural rubber exports to South Korea. 4) GDP per capita in the long and short term has a positive and significant effect on Indonesian natural rubber exports to South Korea. 5) Long-term inflation has a positive and significant effect on Indonesian natural rubber exports to South Korea. Meanwhile, in the short term, inflation has a negative and significant effect on Indonesian natural rubber exports to South Korea.